Shared Academic Governance.. A Historical Perspective - Domenick J Pinto (Academic Chairpersons Conference Proceedings, 2022)
Shared academic governance is a key to ensuring that faculty and administration can work collaboratively to reach strategic planning outcomes, maintain excellence and show continued growth and collegiality in higher education. This workshop will elaborate on experiences I have had in both a university senate and academic assembly, present scenarios that the group can brainstorm on, and conclude with suggestions on how all faculty can become involved.
Keywords: academic; governance; shared; collegiality; faculty; administration